RELIC MIRES IN PENINSULAR ITALY AND NATURA 2000 - F. SPADA (Annali di Botanica, 2007)
The study aims to detect patterns of distribution of mires along a geographical gradient. In order to do this, data from Natura 2000 inventories and distributional data for a selection of mire species have been compared. All data are referred to the 20 Regions (Administrative Districts) since distributional records of mire habitats and mire species are not yet available in literature sources. The inventory and mapping are in progress.